Role of Science, Technology, Executive, and Public (STEP) in Environmental conservation and waste management and the scenario in Politically and Militarily Conflicted Regions (PMCRs) of the world - Ashraf Zainabi; Obeida Asharf (Annals of Environmental Science and Toxicology - Peertechz Publications, 2022)
Environmental conservation and waste management is a great challenge around the world. The realization of safe water, air, sanitation, and hygiene (WASH) for the world is a distant dream. Barring few developed countries, the rest of the world, and more importantly, the third-world countries are struggling hard to achieve safe WASH. India and China are no exceptions. Given the massive population of these two countries, open defecation issues, unscientific waste disposal practices, and poor health and hygiene infrastructure; achieving safe WASH remains a challenge. While science and technology for the conservation of the environment and waste management are advancing day by day, active participation of the executive and the public is insignificant at least in PMCRs. STEP minus E or/and P can't solve the challenges of environmental conservation and waste management. Safe WASH demands enormous attention from science, technology, executive, and the public (STEP) coherently.